P1.38 Bacterial populations detected within first void urine samples of symptomatic male patients with urethritis. (8th July 2017) - Pond, Marcus; Wagner, Josef; Laing, Ken; Nori, Achyuta; Parkhill, Julian; Butcher, Philip; Sadiq, Tariq
Abstract : Introduction: Applying bacterial 16S rRNA profiling we investigated whether species in first void urine (FVU) differed between men presenting with urethritis symptoms with and without urethral inflammation. Methods: 443 patients prospectively attending a London sexual health clinic were classified, based on clinical presentation and Gram stain as: symptomatic urethritis (URE); symptomatic non-urethritis (SYM); and asymptomatic (ASP). Residual FVU's were tested for [K1] Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Trichomonas vaginalis (TV) and Mycoplasma genitalium (MG) and subjected to bacterial 16S rRNA profiling (variable region v1-2) Differences in bacterial oligotypes across samples were described using partial least square discriminant analysis tested using permutational multivariate analysis of variance (PERMANOVA). The hypothesis tested was: URE have distinct urinary bacterial 16S rRNA profiles compared to SYM and ASP. Results: 286/443 samples met quality control criteria. Among URE [n=79], SYM [n=83], and ASP [n=124], CT, MG, NG and TV prevalence's were: 12.7% (95 CI 6.6–22.5), 13.9% (95CI 7.5–24), 8.9% (95CI 3.9–7.5), 1.3% (95CI 0.1–7.8); 2.4% (95CI 0.4–9.2), 2.4% (95CI 0.4–9.2), 1.2% (95CI 0.1–7.5); 2.4% (95CI 0.6–7.4), 5.7% (95CI 2.5–11.8), NG not detected, 0.8% (95CI 0–5.1) respectively. Lactobacillus iners was the most abundant oligotype observed in all groups. Streptococcus agalactiae and S. anginosus were highly dominant in ASP along with S. mitis, which was relatively increased in both ASP and SYM. A decreased relative abundance of these oligotypes was observed in URE cases. A significant difference in oligotype populations was observed between URE and SYM (PERMANOVA test p=0.0072, F2.182), but not between SYM and ASP (PERMANOVA test [JW2] p=0.0.1797, F1.601). Conclusion: SYM and ASP oligotype populations were dominated by Lactobacillus and Streptococcus species. Microbiota observed in FVU samples of symptomatic patients with microscopy confirmed urethritis (URE) were distinct to those with symptoms but no urethritis on microscopy (SYM).